Inovasi Mahasiswa Kampus Mengajar Dalam Meningkatkan Efektivitas Pembelajaran SDN Cihaur - Ardi Afriansyah (Kreativasi : Journal of Community Empowerment, 2024)
The Covid-19 pandemic has had a significant impact on the education sector, forcing a change from conventional learning to online learning. This situation is a special challenge for elementary school teachers who are used to face-to-face learning. This article discusses the Class 1 Teaching Campus Program as the Indonesian government's response to improving the quality of education in the midst of the pandemic. This program involves students in providing teaching assistance in elementary schools in various regions. The main focus is to develop students' interpersonal and technical skills and make a positive contribution to the learning process in elementary schools. The program implementation method involves preparation, implementation, observation, and design. In the teaching stage, students succeeded in increasing students' motivation and interest in learning, while teachers and schools found it easy to implement online and offline learning. This program has also succeeded in adapting technology to support learning, including the use of laptops and MS Excel applications. The evaluation results show a positive impact on students' abilities and ease of learning management for teachers. The Batch 1 Teaching Campus Program at Cihaur State Elementary School, Sukabumi Regency, West Java, can be considered successful in increasing the effectiveness of learning during the pandemic emergency. Increasing student interest in learning and adapting technology are important points in dealing with sudden changes in the learning system. This program creates positive integration of values ​​in the social and educational system in Cihaur Village. Therefore, it is important to implement this kind of collaborative activity widely to support improving the quality of education in the future.